Evidence to inform the future for maternal and newborn health. (October 2016) - Lawn, Joy E.; Blencowe, Hannah; Kinney, Mary V.; Bianchi, Fiorella; Graham, Wendy J.
Abstract : Despite the impressive progress gains for maternal and child health during the Millennium Development Goals era, over 5.6 million women and babies died in 2015 due to complications during pregnancy, birth and in the first month of life. In order to achieve the new mortality targets set out in the Sustainable Development Goals, there needs to be intentional efforts to maintain and accelerate action to end preventable maternal and newborn deaths and stillbirths. This paper outlines what progress is required to meet these new 2030 targets based on patterns of progress in the recent past; where the burden is the greatest; when to focus attention along the continuum of care; and what causes of death require concerted efforts. Priority actions include intentional and intensified political attention and investment in maternal-newborn health with particular focus on improving quality and experience of care around the time of birth with implementation at scale of integrated maternal-newborn health interventions across the continuum of care with commensurate investment targeted at the most vulnerable populations. Looking forward, improved data for decision making and accountability will be required. The health and survival of babies and their mothers are inextricably linked, and calls for coordinated efforts and innovation before and during pregnancy, in childbirth, and postnatally, in order to end preventable maternal, neonatal deaths and stillbirths. Highlights: A high proportion of deaths during pregnancy, birth and the first month of life are preventable. Increased attention and investment in maternal and newborn health requires action now. Improved data for decision-making and accountability are essential to achieving 2030 targets.